Rancang Bangun Multi Pipe Heat Exchanger Pendingin Air Mesin Asap Cair - Naufal, Gostsa Khusnun; Ma'mun, Hisyam (CV. IRA PUBLISHING, 2023)
Liquid smoke is a natural pesticide that can be produced quickly and has a low production price. Making liquid smoke is a combustion process carried out with limited air and as little fire as possible, only embers. Then, the smoke from the combustion process with limited air is channeled into a pipe with a cooling system separate from the combustion chamber. This research used a passive cooling system, soaking the heat exchanger pipe with water. The temperature of the smoke produced is kept stable in the range of 80-90 degrees Celsius. The heat exchanger pipe in this research is designed to reduce the heat from the smoke produced by combustion without producing significant air resistance. The most essential requirement is that it can be made with available materials and has low manufacturing difficulty. In selecting a prototype, a heat exchanger system design was produced using a 1.5-inch diameter iron pipe, easily found on the market. The flow of smoke to be cooled through the heat exchanger pipe is from top to bottom, preventing the resulting liquid from being trapped in the curves of the pipe and making it easier for air and smoke that is still hot to remain at the top of the pipe naturally.